Oil tank bottoms, bacteria isolate after diesel treatment - water and centrifugation - Gonzáles, Marilina (2022)
In the oil industry, large quantities of hydrocarbons are stored in tanks, in the different stages of extraction and processing of crude oil until it is refined. This generates a residue called a tank bottom, which is a stable emulsion of water and hydrocarbon sediments. The objective of this work was to study the bacteria that are present in the sediment after treating the bottom of the tank with diesel oil, water, and subsequent centrifugation. A bottom and tank were treated with diesel, water and centrifugation, the sediment was obtained, which was counted, isolated and bacteria were identified. 34 strains were obtained, of which 86.1% belonged to the genus Bacillus. The same capacity capabilities to develop diesel, kerosene, hexadecane, and cyclohexane hydrocarbons.